Efectividad de la terapia dialéctica conductal para disminuir la desregulación emocional en adultos con trastorno límite de la personalidad - Feliu Pardo, Maria Jose (2021)
Emotional dysregulation is one of the central characteristics within the symptoms of borderline personality disorder (BPD) and one of the most common treatments for this disorder is the dialectical behavior therapy (DBT). The objective of this study is to identify the effectiveness of DBT in reducing emotional dysregulation in adult patients with BPD. For this purpose, a review of the current literature was carried out, analyzing the methodological quality of the data and taking into account the guidelines of the PRISMA guide (Urrútia & Bonfill, 2013). SCOPUS, Proquest, EBSCOhost and ScienceDirect databases were used, with predetermined inclusion and exclusion criteria, ensuing the selection of nine articles. As a result, it was observed a reduction in the emotional dysregulation of patients with BPD, proving the efficacy of DBT in BPD population. Future research should explore which specific processes of DBT treatment enhance changes in strategies to regulate emotions and specify which of these strategies are related to the rest of the BPD symptoms.